2017
DOI: 10.1007/s00214-017-2060-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of the site-specific self-cleavage of the RNA phosphodiester backbone by a twister ribozyme

Abstract: isotope effects on the nucleophile and leaving oxygen atoms, in very good agreement with experiments, also support this description. Nevertheless, the free energy profiles in the enzyme and in solution are almost coincident which, despite that the rate-limiting activation free energy is in very good agreement with experimental data of counterpart reactions in solution, rule out this substrate-assisted catalysis mechanism for the twister ribozyme from O. sativa. Catalysis must come from the role of alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…The definition of the limits of an "active" inline attack geometry was established by York and co-workers, as the one that has an O2′-P′O5′ angle of more than 125° and O2′-P distance of less than 3.5 Å [57]. This behavior is confirmed in previous studies of related models, where reactive conformations appear less often during MD simulations with the calculated probabilities not higher than 7.7% [57][58][59].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 55%
“…The definition of the limits of an "active" inline attack geometry was established by York and co-workers, as the one that has an O2′-P′O5′ angle of more than 125° and O2′-P distance of less than 3.5 Å [57]. This behavior is confirmed in previous studies of related models, where reactive conformations appear less often during MD simulations with the calculated probabilities not higher than 7.7% [57][58][59].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 55%
“…Thus, some general acid and general base present at the active site should be involved in the self-cleavage mechanism. 1274 Notably, in some of the available crystal structures, the U-1(2′-OH) nucleophile was not positioned in an in-line attack conformation relative to the scissile phosphate. 1271 , 1272 The absence of this conformation was explained by crystal packing artifacts, leading to extrusion of the U-1 nucleotide from the active site and rearrangements of the sugar–phosphate backbone around the scissile phosphate.…”
Section: Simulations Of Specific Rna Systemsmentioning
confidence: 99%
“…The theoretical studies with an implicit model of the solvent, as well as the QM/MM calculations, for similar systems to the one studied in the present paper, lead to equivalent energy profiles in which the TS2 is the transition state of highest energy. ,, As it has been mentioned in the Computational Methods section, two options can be envisaged in the use of a continuum model for the solvent: to work with the geometries of the stationary points in gas phase or the geometries optimized in solution. In our case, we have not found notable modifications when optimizing in solution (see Tables and S2), and so the first option becomes acceptable.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 89%
“…Four theoretical studies, using quantum mechanics/molecular mechanics (QM/MM) with a nonpolarizable force field, have shown that this is what happens in the case of the Hairpin ribozyme but not in the Twister ribozyme . In two of these papers, , the proton transfer that activates the nucleophile precedes the nucleophilic attack, while both processes are simultaneous in the other two. , …”
Section: Introductionmentioning
confidence: 99%